THE DIFFERENCE ON COMPRESSIVE STRENGTH AND DIMENSIONAL CHANGE OF COMMERCIALLY TYPE III GYPSUM COMPARED TO RECYCLE GYPSUM TYPE III TO PRODUCE WORKING CAST: PERBEDAAN KEKUATAN KOMPRESI DAN PERUBAHAN DIMENSI GIPSUM TIPE III KOMERSIAL DENGAN GIPSUM TIPE III DAUR ULANG UNTUK MODEL KERJA GIGI TIRUAN - Wahyuni, Siti; Tamin, Haslinda Z; Agusnar, Harry (Dentika: Dental Journal, 2016)
Gypsum is derived from pure calcium sulfate dehydrate which is a common material that is commonly used in denture manufacturing process. This study aimed to know the difference on compressive strength and dimensional change of commercially type III gypsum compared to recycle type III gypsum to produce working cast. The type of research is laboratory experiment. A total of 40 samples for each test is divided into five groups which consists of commercial type III gypsum, pure recycled type III gypsum, pure recycled type III gypsum with 10%, 20%, 30% type III commercial gypsum. The difference on compressive strength and dimensional change between the groups was analyzed using one way ANOVA and is them tested with LSD test. The result showed that there was a significant difference (p<0,05) between compressive strength and dimensional change of commercial type III gypsum compared to pure recycled type III gypsum and pure recycled type III gypsum with 10%, 20% and 30% type III commercial gypsum. In conclusion, addition of 30% commercial gypsum in recycled gypsum the compressive strength was higher than other recycled gypsum types.